Tari Bujang Ganong Untuk Menstimulasi Kreativitas Remaja di Sanggar Ngesti Broto - Adventi, Brigita; Sari, Wayan; Saputri, Amelia Hani; Bulan, Indra (Journal of Student Development Information System (JoSDIS), 2025)
Bujang Ganong Dance is one of the traditional art forms originating from Java, which has high cultural and aesthetic values. This study aims to explore the role of Bujang Ganong Dance in stimulating adolescent creativity at the Ngesti Broto Studio. The method used in this study is a qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that participation in Bujang Ganong Dance has a positive impact on the development of adolescent creativity, both in terms of dance art and in terms of social and emotional aspects. Adolescents involved in this studio show an increase in their ability to collaborate, communicate, and express themselves. In addition, this activity also contributes to the preservation of local culture and builds a sense of pride in cultural heritage. The conclusion of this study confirms that Bujang Ganong Dance not only functions as a means of entertainment, but also as an effective tool for developing adolescent creativity and character in the modern era. This study is expected to provide insight for art studio managers and educators in designing more effective programs for the development of adolescent creativity.